The implementation of strategic partnering in industrialised building system / Faridah Muhamad Halil - Muhamad Halil, Faridah (Institute of Graduate Studies, UiTM, 2013)
The concept of strategic partnering is an important consideration for the players in the construction industry. The research has revealed that strategic partnering is about long term relationship practiced between two or more parties in projects awarded by the clients. Strategic partnering in construction has been presented as a potentially important way of improving construction project performance through the direct benefits received by the clients such as quality, project success, less delay, less problem, social benefits and sustainable business. The aim of the research is to develop a conceptual framework for the implementation of strategic partnering in the industrialised building system. The methodology adopted in this research is mixed method consisting of literature search, questionnaire survey and semi-structured interviews. The benefits of using this method are that it presents an opportunity to seek verification in the results from different methods, and also to seek similar or different pattern as well. Using this approach, the targeted of respondents are selected are public and private clients. The findings of this research are derived from the literature review, questionnaire survey and semi structured interviews…